Bentang budaya: Identifikasi Aktivitas Manusia dalam ruang bentuklahan proses fluvial di Tempuran Opak Oyo Yogyakarta - Sitohang, Lidya Lestari; Wicaksono, Krisna Jadug Setyo; Sai’dah, Ety Amelia; Masrifah, Fizah; Fahruddin, Ahmad Faiq (Jurnal Pendidikan Geografi Undiksha, 2025)
One particularly intriguing phenomenon within the geosphere is the cultural landscape observed at Tempuran Opak Oyo. This site, where the Opak River meets the Oyo River, forms a fluvial landform that naturally developed within Bantul Regency in the Special Region of Yogyakarta. This article seeks to examine the effects of human activities on this environment. A qualitative descriptive approach is employed, utilizing literature review, field observation, and expert interviews. The study finds that local residents engage in land uses that rely heavily on natural resources like agriculture, sand mining, and mixed gardens. It also notes that while these activities have certain benefits for the community, they raise concerns about environmental sustainability.